Cytotoxic T lymphocytes recognize influenza haemagglutinin that lacks a signal sequence - Townsend, A; Bastin, J; Gould, K; Brownlee, G (1986)
A surprising feature of most cytotoxic T lymphocytes (CTL) responding to influenza infection is that they recognize the unglycosylated (non-transmembrane) proteins of the virus, including the nucleoprotein. Recognition of cells that express nucleoprotein by CTL does not depend on a definite signal sequence within the protein, and the epitopes recognized can be defined with short synthetic peptides in vitro. Haemagglutinin (HA), the major transmembrane protein of the virus, is recognized by a minor population of CTL from infected mice. We have deleted the sequence coding for the N-terminal signal peptide from a complementary DNA encoding HA of the H1 subtype. The signal-deleted HA is detected with antibodies as a short-lived, unglycosylated, intracellular protein. However, CTL raised to the complete molecule recognize cells expressing the signal-deleted HA and vice versa. These results cast doubts on the assumption that CTL recognize the HA molecule only after its insertion into the plasma membrane.